2007
DOI: 10.1016/j.cardiores.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of carbohydrate and fat intake on pathological left ventricular hypertrophy

Abstract: Currently, a high carbohydrate/low fat diet is recommended for patients with hypertension; however, the potentially important role that the composition of dietary fat and carbohydrate plays in hypertension and the development of pathological left ventricular hypertrophy (LVH) has not been well characterized. Recent studies demonstrate that LVH can also be triggered by activation of insulin signaling pathways, altered adipokine levels, or the activity of peroxisome proliferator-activated receptors (PPARs), sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 196 publications
(289 reference statements)
2
56
0
4
Order By: Relevance
“…Our results support this concept given that in vivo myocyte hypertrophy (cross-sectional area) was reduced in our HFSAT group compared with our HFNC group. A low-carbohydrate/ high-fat diet has been associated with a reduced stimulation of the insulin signaling pathway, resulting in decreased cardiac growth, contractile dysfunction, and gene expression in response to hypertension (37). Interestingly, we (7) recently reported that HF animals fed a SAT diet exhibited preserved myocardial contractile function under conditions of myocardial insulin resistance and alterations in insulin signaling, specifically, diminished activation of Akt and increased total glycogen synthase kinase 3␤.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results support this concept given that in vivo myocyte hypertrophy (cross-sectional area) was reduced in our HFSAT group compared with our HFNC group. A low-carbohydrate/ high-fat diet has been associated with a reduced stimulation of the insulin signaling pathway, resulting in decreased cardiac growth, contractile dysfunction, and gene expression in response to hypertension (37). Interestingly, we (7) recently reported that HF animals fed a SAT diet exhibited preserved myocardial contractile function under conditions of myocardial insulin resistance and alterations in insulin signaling, specifically, diminished activation of Akt and increased total glycogen synthase kinase 3␤.…”
Section: Discussionmentioning
confidence: 97%
“…In consideration of the comorbidities associated with HF (e.g., obesity, hypertension, and diabetes), dietary guidelines have traditionally recommended a low-fat/high-carbohydrate diet for coronary artery disease patients (19), although these recommendations are currently under revision (16, 42). Nonetheless, high dietary fat, particularly saturated fat, has long been implicated with myocardial lipid accumulation, contractile and mitochondrial dysfunction, apoptotic cell death, enhanced ventricular remodeling, and cardiac hypertrophy (35,37).Given the heart's limited capacity to store lipids, coupled with a decrease in the ␤-oxidation of fatty acids in HF, it has been suggested that excessive fat intake may increase the propensity for lipotoxicity (22,23,35), ultimately leading to contractile dysfunction. In contrast to the proposed lipotoxic effects on contractile function, we have previously reported no further progression of HF/LV dysfunction in rats fed a highsaturated fat (SAT) diet postinfarction compared with rats fed normal chow (NC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Production of selective reactive oxygen species in the adipose tissue of obese mice leads to the development of inflammatory processes and to the dysregulation of adipocytokines, including adiponectin, plasminogen activator inhibitor-1 and IL-6 (13). Furthermore, a variety of dietary components may play significant roles in the development of insulin resistance (14), which may affect the progression of diabetes (15), hepatic steatosis (16), cardiovascular disease and hypertension (17).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that suggests a potential relationship between insulin resistance and cardiac hypertrophy (21,22). Therefore we examined plasma glucose and insulin levels in mice subjected to chronic pressure overload.…”
Section: Figurementioning
confidence: 99%